2017
DOI: 10.1364/oe.25.021901
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot white light emitting diodes with high scotopic/photopic ratios

Abstract: Alloy core/shell CdZnS/ZnS quantum dots (QDs) are emerging as robust candidates for light-emitting diodes (LEDs), however the emission range of the current CdZnS/ZnS is quite limited, ranging from 390 to 470 nm. It still remains a challenging task to construct white LEDs based on current CdZnS/ZnS system. Here, a versatile ZnSe with a moderate band gap is introduced onto the CdZnS core. The ZnSe shell, on one hand, can passivate the core surface which leads to bright emissions. On the other hand, it is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Based on these findings, Liu et al [209] (Fig.20g). Previous studies suggest that the defects on the surface of traditional semiconductors can significantly be passivated by incorporating a shell on the surface of QD, which leads to improved photoluminescence (PL) and quantum efficiency [217]. Li et al [218] successfully fabricated core-shell constructed QDs on CsPbBr 3 device which exhibited outstanding photovoltaic properties including tunable energy levels and high luminescence and realized a champion PCE of 8.65% which was 14.8% higher than the pristine cell (Fig.20h)…”
Section: Ionic Liquids (Ils) Interface Engineeringmentioning
confidence: 98%
“…Based on these findings, Liu et al [209] (Fig.20g). Previous studies suggest that the defects on the surface of traditional semiconductors can significantly be passivated by incorporating a shell on the surface of QD, which leads to improved photoluminescence (PL) and quantum efficiency [217]. Li et al [218] successfully fabricated core-shell constructed QDs on CsPbBr 3 device which exhibited outstanding photovoltaic properties including tunable energy levels and high luminescence and realized a champion PCE of 8.65% which was 14.8% higher than the pristine cell (Fig.20h)…”
Section: Ionic Liquids (Ils) Interface Engineeringmentioning
confidence: 98%
“…However, the emission wavelengths of pure core CdZnS or CdZnSe QDs are quite limited (ranging from 400 to 475 nm for CdZnS QDs and from 500 to 620 nm for CdZnSe ones) [3,13,17], which restricts their further applications. In our previous work, after introducing a versatile ZnSe shell with a moderate bandgap (2.7 eV) upon the CdZnS and the CdZnSe cores, the emission wavelength of the resulting CdZnS/ZnSe and CdZnSe/ZnSe QDs is extended to the deep-red region (680 nm) [18,19]. Emission tunable CdZnSe QDs can been achieved by tuning the Cd : Zn ratio by incorporating the control of the reaction time and/or temperature [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Lita et al [14] reported a light source with an S/P ratio of 2.56 at a correlated colour temperature (CCT) of 5368 K. Nizamoglu et al [15] reported a white-light emitting diode (WLED) with an S/P ratio of 3.04 at the extremely high CCT of 45000 K. Guo et al [16] proposed light-emitting diodes (LEDs) for CCTs from 2700 K to 45000 K with S/P ratios in the range from 1.83 to 3.84. Zan et al [17] reported WLEDs that reached S/P ratios from 1.54 to 3.84, which corresponded to CCTs in the range from 2700 K to 7580 K. Li et al [18] reported two-hump quantum-dot-based LEDs that reached an S/P ratio value of 2.09 at 4038 K, and a four-hump LED that reached an S/P ratio value of 3.08 at 5015 K. Zhang et al [19] optimised hybrid white LEDs for high S/P ratios at varying CCTs that reached high colour rendition, and compared their differences. Despite the fact that in some studies it has not been mentioned which SSC was used, we rechecked the spectra in the literature and have confirmed that most studies have used 2-degree SSCs.…”
Section: Introductionmentioning
confidence: 99%